Reaching out to Users: Romanian Academic Libraries on Facebook - Madge, Octavia-Luciana (Qualitative and Quantitative Methods in Libraries, 2017)
Lately, most academic libraries have been experimenting with different innovative methods for improving their information services and for reaching out to their users who display new information practices and expectations. The advance of the new technologies and the variety of applications available nowadays offer the necessary context for academic libraries to try new formats for delivering information. One of these new ways is to use social networks, such as Facebook or MySpace, in order to communicate better with the users and to provide them with specialized assistance. This paper analyzes the presence of large Romanian academic libraries on Facebook, how they use this outreach tool and what information they deliver through their Facebook page.